Molecular Characterization of Bovine Leukemia Virus with the Evidence of a New Genotype Circulating in Cattle from Kazakhstan - Akhmetzhan Sultanov; Marzena Rola-Łuszczak; Saltanat Mamanova; Anna Ryło; Zbigniew Osiński; Meruyert A. Saduakassova; Elvira Bashenova; Jacek Kuźmak (Pathogens, 2022)
Bovine leukemia virus (BLV) is a retrovirus that causes enzootic bovine leukosis (EBL) and has worldwide distribution. Infections with BLV have been reported in cattle from Kazakhstan but the virus has not yet been thoroughly characterized. In this study, we detect and estimate the level of BLV proviral DNA by qPCR in DNA samples from 119 cattle naturally infected with BLV, from 18 farms located in four different geographical regions of Kazakhstan. Furthermore, we conducted the phylogenetic and molecular analysis of 41 BLV env-gp51 gene sequences from BLV infected cattle. Phylogenetic analysis showed the affiliation of sequences to two already known genotypes G4 and G7 and also to a new genotype, classified as genotype G12. In addition, a multivariate method was employed for analysis of the association between proviral load and different variables such as the geographical location of the herd, cattle breeds, age of animals, and the presence of particular BLV genotypes. In summary, the results of this study provide the first evidence on molecular characterization of BLV circulating in cattle from Kazakhstan.